RANCANG BANGUN MESIN PENGAYAK PASIR OTOMATIS - Betti Ses Eka Polonia; Helanianto Helanianto; Hendri Kurniawan (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
Sand is an important material in building construction for residential houses, places of worship, offices, educational facilities, and other buildings. Sand generally consists of sand mixed with gravel and stone. An automatic sand sieving machine makes separating rock gravel from sand easier. Making an automatic sand sieving machine aims to get better quality and cleaner sand screening results. This sand sifter machine is made to prevent the entry of gravel in the sieving process. In addition, the sand sieving process can be more efficient and effective. The automatic sand sieving machine has dimensions of 100 cm long, 70 cm wide, and 80 cm high. The test results of the sand sieving machine can sift sand with a capacity of 5 kg in 15 seconds and a sand capacity of 10 kg in 32 seconds.